Looking out, looking in (Thomson, 2008)
LOOKING OUT/LOOKING IN, is the leading interpersonal communication book in print. Written in a reader-friendly voice that links scholarship to users' everyday lives, this popular book motivates readers to improve their interpersonal skills and sharpen their critical understanding of the process of communication. Through thoughtful, diverse examples that include fine art, music, poetry, film, and more, users can consistently see the importance of interpersonal communication and how it affects their society and their lives.